The potential roles of interleukin-25 in infectious diseases - Wu, Jing; Zhang, Fang; Tao, Hongji; Nawaz, Waqas; Chen, Deyan; Wu, Zhiwei (Frontiers in Immunology, 2022)
Interleukin-25 (IL-25), also known as IL-17E, is a recently identified cytokine of the IL-17 family. Numerous studies illustrated that the expression of IL-25 is regulated by multiple pathogens, including parasitic, viral, and bacterial infections. IL-25 has a dual function in infectious diseases. On the one hand, IL-25 activates type 2 immunity via the relevant cytokines, including IL-4, IL-5, and IL-13, which are associated with the development of pathogenic infection-related allergic diseases. On the other hand, IL-25 involves in the recruitment of group 2 innate lymphoid cells (ILC2) to enhanced T helper 2 (Th2) cell differentiation, which are important to the clearance of pathogens. However, the precise roles of IL-25 in infectious diseases remain largely unknown. Thus, the current review will shed light on the pivotal roles of IL-25 in infectious diseases.